Negative electrode material based on modified carbon nanotubes and preparation method thereof

By combining modified carbon nanotubes and modified nanosilicon, a stable conductive network structure is formed, which solves the problem of capacity attenuation and short cycle life of the negative electrode material of lithium-ion battery during fast charging and discharge, and achieves a significant improvement in capacitance and cycling performance.

CN119695150AInactive Publication Date: 2025-03-25JIANGSU SMART WORKSHOP TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411710922.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries have problems such as capacity attenuation and short cycle life during fast charging and discharging, especially in harsh environments, and performance is difficult to ensure.

Method used

The combination of modified carbon nanotubes and modified nanosilicon is adopted to improve the uniformity and interface stability of the material through modification treatment to form a stable conductive network structure. The specific steps include pretreating the carbon nanotubes and nanosilicon, and then forming a composite material of modified carbon nanotubes and nanosilicon through silane modification, epoxidation treatment and addition of surfactant.

Benefits of technology

The capacitance and cycling performance of lithium batteries have been significantly improved, especially at normal temperature, low temperature and high temperature conditions, and the first Coulomb efficiency has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155697140000111
    Figure BDA0005155697140000111
  • Figure BDA0005155697140000121
    Figure BDA0005155697140000121
Patent Text Reader

Abstract

The invention provides a negative electrode material based on modified carbon nanotubes and a preparation method thereof, and belongs to the technical field of lithium battery materials, the preparation method comprises the following steps: mixing 5.2-5.5 parts by weight of modified nano silicon, 1 part by weight of modified carbon nanotubes, 0.1-0.3 part by weight of a surfactant and 10-12 parts by weight of ethanol, heating to 60-65 DEG C, stirring for 0.5-1 hour, adjusting the pH value to 8.0-8.2 by using ammonia water, and stirring for 0.5-1 hour to obtain the negative electrode material based on modified carbon nanotubes. And then adding 8-10 parts by weight of water, carrying out heat preservation reaction for 12-15 hours, and after the reaction is finished, filtering, washing and drying to obtain the negative electrode material based on the modified carbon nanotubes. The negative electrode material prepared by the invention can be used as a battery negative electrode material, and has the advantages of high capacitance, good cycle performance, excellent high and low temperature resistance and good electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a negative electrode material based on modified carbon nanotubes and a preparation method thereof. Background Art

[0002] The negative electrode material of lithium-ion batteries is usually carbon material. When the battery is charged, lithium ions are deintercalated from the positive electrode, pass through the electrolyte to the negative electrode, and are embedded in the negative electrode material. This process is called lithiation. When discharging, the opposite is true, and lithium ions are deintercalated from the negative electrode and move to the positive electrode.

[0003] Currently, commercial lithium-ion batteries generally use graphite materials as negative electrodes, but their theoretical specific capacity is low, and there is a phenomenon of graphite layer peeling during rapid charge and discharge, resulting in significant capacity decay. Compared with traditional graphite carbon negative electrode materials, silicon-based materials have gradually become an ideal choice for the pursuit of high energy density lithium-ion battery negative electrodes due to their higher theoretical specific capacity. However, silicon materials undergo significant volume changes during the process of lithium ion insertion and extraction, which leads to rapid degradation of their electrochemical performance and a shorter cycle life, thus limiting the promotion of silicon in practical applications.

[0004] In the prior art, carbon nanotubes and silicon particles are used to form a conductive network to improve the effective transmission of electrons between active particles, while buffering the volume expansion of silicon during lithium insertion and extraction, thereby reducing capacity decay. However, it is difficult to ensure the uniformity of the composite of carbon nanotubes and silicon, and the weak bonding force between the silicon and carbon surfaces causes the composite material to fall off from the current collector during lithium insertion and extraction, thereby causing the specific capacity to decay rapidly. Especially in harsh environments, the performance of the battery is difficult to guarantee.

[0005] Therefore, there is an urgent need for a negative electrode material based on modified carbon nanotubes and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide a negative electrode material based on modified carbon nanotubes and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a negative electrode material based on modified carbon nanotubes comprises the following steps:

[0009] Step 1: Preparation of modified carbon nanotubes:

[0010] (1) mixing carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 1: (30-35), stirring evenly, heating in a water bath at 50-60° C. for 2-3 h, washing with water until neutral, and drying to obtain pretreated carbon nanotubes;

[0011] (2) adding 1 part by weight of the pretreated carbon nanotubes to 90-100 parts by weight of a mixed solvent of ethanol / water, adjusting the pH to 9-9.5 with 30 wt% ammonia water, dropping 2.0-2.5 parts by weight of KH550, reacting at 40-45° C. for 12-15 h, filtering, washing, and drying to obtain silane-modified carbon nanotubes;

[0012] (3) dispersing 0.5 parts by weight of silane-modified carbon nanotubes in 50-55 parts by weight of dimethylformamide, adding 1.5-1.7 parts by weight of unsaturated monomers containing epoxy groups and 1.5-1.7 parts by weight of monomers containing carbon-carbon double bonds, heating to 60-65° C. under nitrogen protection, adding 0.13-0.15 parts by weight of azobisisobutyronitrile, and continuing to heat to 80-85° C., reacting for 3-5 hours, cooling to room temperature, washing, and drying to obtain modified carbon nanotubes;

[0013] Step 2: Preparation of modified nano-silicon:

[0014] (1) placing nano-silicon in a H2SO4 / H2O2 mixed solution with a volume ratio of (3-4):1, stirring at 80-90°C for 2-3h, filtering, washing, and drying to obtain pretreated nano-silicon;

[0015] (2) dissolving 1 part by weight of pretreated nano-silicon and 0.3-0.5 parts by weight of 3-aminopropyltriethoxysilane in 12-15 parts by weight of anhydrous toluene, reacting under reflux at 60-70° C. for 20-22 hours, separating the solid from the liquid, washing, and vacuum drying to obtain modified nano-silicon;

[0016] Step 3: Preparation of negative electrode materials:

[0017] (3) 5.2-5.5 parts by weight of modified nano-silicon, 1 part by weight of modified carbon nanotubes, 0.1-0.3 parts by weight of a surfactant and 10-12 parts by weight of ethanol are mixed, the temperature is raised to 60-65°C, and the mixture is stirred for 0.5-1h. The pH value is adjusted to 8.0-8.2 with aqueous ammonia, and then 8-10 parts by weight of water are added. The mixture is kept warm for reaction for 12-15h. After the reaction is completed, the mixture is filtered, washed and dried to obtain a negative electrode material based on modified carbon nanotubes.

[0018] Furthermore, the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is (3-4):1.

[0019] Furthermore, the volume ratio of ethanol to water in the ethanol / water mixed solvent is (3-4):1.

[0020] Furthermore, the epoxy group-containing unsaturated monomer includes glycidyl methacrylate and allyl glycidyl ether in a weight ratio of (2-4):1.

[0021] Furthermore, the monomer containing carbon-carbon double bonds comprises methyl methacrylate, isooctyl methacrylate and butyl acrylate in a weight ratio of 1:(1.2-1.4):(0.3-0.6).

[0022] At present, adding carbon nanotubes to nano-silicon to prepare electrode materials for lithium-ion batteries is a common research direction, because this combination can utilize the excellent conductivity and mechanical stability of carbon nanotubes to improve the performance of nano-silicon. However, carbon nanotubes and nano-silicon are prone to agglomeration when mixed, which will affect the uniformity of the material and thus reduce the efficiency and life of the electrode. The present invention can improve the capacity of the battery by modifying the carbon nanotubes. The analysis is that the modified carbon nanotubes, the introduced groups (such as epoxy groups, etc.) can form a protective film on the surface of the carbon nanotubes, produce a steric hindrance effect, and prevent the carbon nanotubes from approaching each other and re-aggregating.

[0023] Furthermore, the particle size of the nano-silicon is 10-50nm, the average particle size is 35nm, and the specific surface area is 42.4m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0024] Furthermore, the carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:(1.2-1.5):(0.6-0.8).

[0025] Furthermore, the single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g, conductivity is 2400s / cm; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​450m 2 / g, conductivity is 150s / cm; the diameter of multi-walled carbon nanotubes is 5-15nm, the length is 0.5-2μm, and the specific surface area is 45m 2 / g, conductivity is 120s / cm. It was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0026] In order to improve the room temperature cycle performance of the battery, the present invention modifies the nano-silicon so that the amino groups on the modified nano-silicon react with the epoxy groups on the modified carbon nanotubes, thereby improving the room temperature cycle performance of the battery. Analysis shows that a more stable interface connection is established between the nano-silicon and the carbon nanotubes through the formation of stable chemical bonds, and this connection can reduce the performance degradation caused by the separation between the materials during the charge and discharge process.

[0027] In the actual application process, many application scenarios require lithium batteries to work in high temperature environments, such as the operation of electric vehicles in hot weather, the use of aerospace vehicles in tropical areas, and the deployment of energy storage systems in high temperature areas; in cold areas or in winter, vehicles need to start in low temperature environments. At this time, the battery needs to have sufficient energy output capacity, and many portable electronic devices also need to work normally under low temperature conditions. Good low-temperature cycle performance can ensure that the battery can still provide sufficient power support under low temperature conditions. However, most of the negative electrode materials on the market currently only focus on the cyclability at room temperature and cannot be applied to a variety of applicable scenarios in actual applications. The present invention uses carbon nanotubes with specific parameters and nano-silicon with specific particle sizes to improve the cycle performance of lithium batteries at high temperatures. Because carbon nanotubes have excellent conductivity, they can effectively improve the electron conduction capacity inside the battery. At the same time, carbon nanotubes with specific parameters can provide the best conductive network structure, so that a good electron transmission path can still be maintained under high temperature conditions, and the nano-silicon with specific parameters can be more evenly dispersed between the above-mentioned carbon nanotubes, forming a stable conductive network through chemical bonds and the like, improving the conductivity of the electrode material, and improving the charge and discharge efficiency. And when using a specific ratio of unsaturated monomers containing epoxy groups and monomers containing carbon-carbon double bonds, the cycle performance of lithium batteries at low temperatures can be further improved. The analysis shows that a stable three-dimensional network structure can be formed between unsaturated monomers containing epoxy groups and monomers containing carbon-carbon double bonds in a specific ratio, which can improve the low-temperature electronic conductivity of the material. At the same time, the ratio of the monomers will affect the distribution of epoxy groups on the surface of carbon nanotubes, further affecting the interface stability between nanosilicon and carbon nanotubes. This enhanced interface stability helps to reduce the separation of electrode materials under low temperature conditions and improve the cycle performance.

[0028] Furthermore, the surfactant is a mixture of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1: (1.2-1.4): (0.3-0.6).

[0029] The first coulombic efficiency refers to the ratio of the discharge capacity to the charge capacity of the battery during the first charge and discharge cycle. The first coulombic efficiency of lithium-ion batteries is closely related to the negative electrode material. Generally, silicon-based materials have a low first coulombic efficiency due to their large volume changes. The present invention can improve the coulombic efficiency of the battery by adding a surfactant with a specific ratio. The analysis shows that by adding a surfactant, the modified nano-silicon can be more evenly combined with the modified carbon nanotubes through chemical bonds to form a more ordered silicon-carbon composite phase to form a more stable structure, which reduces the expansion rate of the material, and can effectively improve the first coulombic efficiency of the lithium-ion battery.

[0030] The present invention also provides a negative electrode material based on modified carbon nanotubes prepared by the above preparation method.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0032] 1. The present invention can improve the capacity of the battery by modifying the carbon nanotubes.

[0033] 2. The present invention improves the room temperature cycle performance of the battery by modifying the nano-silicon to allow the amino groups on the modified nano-silicon to react with the epoxy groups on the modified carbon nanotubes.

[0034] 3. The present invention uses carbon nanotubes with specific parameters and nano silicon with specific particle size to improve the cycle performance of lithium batteries at high temperatures. And uses unsaturated monomers containing epoxy groups and monomers containing carbon-carbon double bonds in specific ratios to further improve the cycle performance of lithium batteries at low temperatures.

[0035] 4. The present invention can improve the coulombic efficiency of the battery by adding a surfactant in a specific ratio. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The raw materials used in the following examples of the present invention are all commercially available products:

[0038] Concentrated sulfuric acid,

[0039] Concentrated nitric acid,

[0040] Example 1

[0041] This embodiment provides a method for preparing a negative electrode material based on modified carbon nanotubes, comprising the following steps:

[0042] Step 1: Preparation of modified carbon nanotubes:

[0043] (1) mixing carbon nanotubes, concentrated sulfuric acid (70% by mass) and concentrated nitric acid (68% by mass) in a weight ratio of 1:32, stirring evenly, heating in a water bath at 55° C. for 2.5 h, washing with water until neutral, and drying to obtain pretreated carbon nanotubes;

[0044] The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is 3.5:1.

[0045] The carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:1.4:0.7. The single-walled carbon nanotubes have a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g, conductivity is 2400s / cm; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​450m 2 / g, conductivity is 150s / cm; the diameter of multi-walled carbon nanotubes is 5-15nm, the length is 0.5-2μm, and the specific surface area is 45m 2 / g, conductivity is 120s / cm. It was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0046] (2) adding 1 part by weight of the pretreated carbon nanotubes to 95 parts by weight of a mixed solvent of ethanol / water, adjusting the pH to 9.2 with 30 wt% ammonia water, dropping 2.2 parts by weight of KH550, reacting at 42° C. for 14 h, filtering, washing, and drying to obtain silane-modified carbon nanotubes;

[0047] The volume ratio of ethanol to water in the ethanol / water mixed solvent is 3.5:1.

[0048] (3) dispersing 0.5 parts by weight of silane-modified carbon nanotubes in 52 parts by weight of dimethylformamide, adding 1.6 parts by weight of unsaturated monomers containing epoxy groups and 1.6 parts by weight of monomers containing carbon-carbon double bonds, heating to 62° C. under nitrogen protection, adding 0.14 parts by weight of azobisisobutyronitrile, and continuing to heat to 82° C., reacting for 4 hours, cooling to room temperature, washing, and drying to obtain modified carbon nanotubes;

[0049] The unsaturated monomer containing epoxy group comprises glycidyl methacrylate and allyl glycidyl ether in a weight ratio of 3:1.

[0050] The monomer containing carbon-carbon double bonds includes methyl methacrylate, isooctyl methacrylate and butyl acrylate in a weight ratio of 1:1.3:0.5.

[0051] Step 2: Preparation of modified nano-silicon:

[0052] (1) placing nano-silicon in a H2SO4 / H2O2 mixed solution (H2SO4 mass fraction is 60%, H2O2 mass fraction is 3%) with a volume ratio of 3.6:1, stirring at 85°C for 2.6 hours, filtering, washing, and drying to obtain pretreated nano-silicon;

[0053] The particle size of the nano-silicon is 10-50nm, the average particle size is 35nm, and the specific surface area is 42.4m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0054] (2) dissolving 1 part by weight of pretreated nano-silicon and 0.4 parts by weight of 3-aminopropyltriethoxysilane in 14 parts by weight of anhydrous toluene, reacting at 65° C. for 21 hours, separating the solid from the liquid, washing, and vacuum drying to obtain modified nano-silicon;

[0055] Step 3: Preparation of negative electrode materials:

[0056] (3) 5.4 parts by weight of modified nano-silicon, 1 part by weight of modified carbon nanotubes, 0.2 parts by weight of a surfactant and 11 parts by weight of ethanol were mixed, wherein the surfactant was a mixture of polyvinyl pyrrolidone K30 (purchased from Jinan Deqiao Chemical Technology Co., Ltd.), sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1:1.3:0.5; the temperature was raised to 62°C, stirred for 0.7h, the pH value was adjusted to 8.1 with ammonia water, and then 9 parts by weight of water was added. The reaction was kept warm for 14h. After the reaction was completed, the negative electrode material based on modified carbon nanotubes was obtained by filtering, washing and drying.

[0057] Example 2

[0058] This embodiment provides a method for preparing a negative electrode material based on modified carbon nanotubes, comprising the following steps:

[0059] Step 1: Preparation of modified carbon nanotubes:

[0060] (1) mixing carbon nanotubes, concentrated sulfuric acid (70% by mass) and concentrated nitric acid (68% by mass) in a weight ratio of 1:30, stirring evenly, heating in a 50° C. water bath for 2 h, washing with water until neutral, and drying to obtain pretreated carbon nanotubes;

[0061] The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is 4:1.

[0062] The carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:1.5:0.8. The single-walled carbon nanotubes have a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g, conductivity is 2400s / cm; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​450m 2 / g, conductivity is 150s / cm; the diameter of multi-walled carbon nanotubes is 5-15nm, the length is 0.5-2μm, and the specific surface area is 45m 2 / g, conductivity is 120s / cm. It was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0063] (2) 1 part by weight of the pretreated carbon nanotubes was added to 90 parts by weight of a mixed solvent of ethanol / water, the pH was adjusted to 9.5 with 30 wt% ammonia water, 2.0 parts by weight of KH550 was added dropwise, the mixture was reacted at 45° C. for 12 h, filtered, washed, and dried to obtain silane-modified carbon nanotubes;

[0064] The volume ratio of ethanol to water in the ethanol / water mixed solvent is 4:1.

[0065] (3) dispersing 0.5 parts by weight of silane-modified carbon nanotubes in 55 parts by weight of dimethylformamide, adding 1.5 parts by weight of unsaturated monomers containing epoxy groups and 1.7 parts by weight of monomers containing carbon-carbon double bonds, heating to 60° C. under nitrogen protection, adding 0.15 parts by weight of azobisisobutyronitrile, and continuing to heat to 80° C., reacting for 5 hours, cooling to room temperature, washing, and drying to obtain modified carbon nanotubes;

[0066] The unsaturated monomer containing epoxy group includes glycidyl methacrylate and allyl glycidyl ether in a weight ratio of 2:1.

[0067] The monomer containing carbon-carbon double bonds includes methyl methacrylate, isooctyl methacrylate and butyl acrylate in a weight ratio of 1:1.4:0.6.

[0068] Step 2: Preparation of modified nano-silicon:

[0069] (1) placing nano-silicon in a H2SO4 / H2O2 mixed solution (H2SO4 mass fraction is 60%, H2O2 mass fraction is 3%) with a volume ratio of 4:1, stirring at 80°C for 3 hours, filtering, washing, and drying to obtain pretreated nano-silicon;

[0070] The particle size of the nano-silicon is 10-50nm, the average particle size is 35nm, and the specific surface area is 42.4m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0071] (2) dissolving 1 part by weight of pretreated nano-silicon and 0.5 parts by weight of 3-aminopropyltriethoxysilane in 15 parts by weight of anhydrous toluene, reacting under reflux at 70° C. for 20 h, separating the solid from the liquid, washing, and vacuum drying to obtain modified nano-silicon;

[0072] Step 3: Preparation of negative electrode materials:

[0073] (3) 5.5 parts by weight of modified nano-silicon, 1 part by weight of modified carbon nanotubes, 0.3 parts by weight of a surfactant and 10 parts by weight of ethanol were mixed, wherein the surfactant was a mixture of polyvinyl pyrrolidone K30 (purchased from Jinan Deqiao Chemical Technology Co., Ltd.), sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1:1.4:0.6; the temperature was raised to 65°C, stirred for 1 hour, the pH value was adjusted to 8.0 with ammonia water, and then 8 parts by weight of water were added, and the reaction was kept warm for 15 hours. After the reaction was completed, the negative electrode material based on modified carbon nanotubes was obtained by filtering, washing and drying.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that the carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:1:1.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that the diameter of the single-walled carbon nanotube is 0.5-8 nm, the length is 20-40 μm, and the specific surface area is 70 m 2 / g, conductivity is 2000s / cm; double-walled carbon nanotubes have a diameter of 5-8nm, a length of 1-4μm, and a specific surface area of ​​300m 2 / g, conductivity is 100s / cm; the diameter of multi-walled carbon nanotubes is 10-20nm, the length is 2-4μm, and the specific surface area is 27m 2 / g, conductivity is 90s / cm. It was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that the unsaturated monomer containing epoxy group comprises glycidyl methacrylate and allyl glycidyl ether in a weight ratio of 1:1.

[0080] Comparative Example 4

[0081] The difference between this comparative example and Example 1 is that the monomer containing carbon-carbon double bonds includes methyl methacrylate, isooctyl methacrylate and butyl acrylate in a weight ratio of 1:1:1.

[0082] Comparative Example 5

[0083] The difference between this comparative example and Example 1 is that the particle size of the nano-silicon is 60-120nm, the average particle size is 100nm, and the specific surface area is 8.3m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0084] Comparative Example 6

[0085] The difference between this comparative example and Example 1 is that the nano-silicon is not modified and a carbonization treatment step is added.

[0086] A method for preparing a negative electrode material based on modified carbon nanotubes comprises the following steps:

[0087] Step 1: Preparation of modified carbon nanotubes: The specific implementation method is the same as that of Example 1;

[0088] Step 2: Preparation of negative electrode materials:

[0089] (3) 5.4 parts by weight of nano-silicon, 1 part by weight of modified carbon nanotubes, 0.2 parts by weight of a surfactant and 11 parts by weight of ethanol were mixed, wherein the surfactant was a mixture of polyvinyl pyrrolidone K30 (purchased from Jinan Deqiao Chemical Technology Co., Ltd.), sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1:1.3:0.5; after being evenly dispersed, the mixture was dried and carbonized at 800°C for 6 hours to obtain a negative electrode material based on modified carbon nanotubes;

[0090] The particle size of the nano-silicon is 10-50nm, the average particle size is 35nm, and the specific surface area is 42.4m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0091] Comparative Example 7

[0092] The difference between this comparative example and Example 1 is that the surfactant is a mixture of polyvinyl pyrrolidone K30 (purchased from Jinan Deqiao Chemical Technology Co., Ltd.), sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1:1:1.

[0093] Comparative Example 8

[0094] The difference between this comparative example and Example 1 is that the surfactant is in a weight ratio of 1:

[0095] Mix Tween 60, Span 80 and sodium lignin sulfonate in a ratio of 1.3:0.5.

[0096] Performance Testing

[0097] The negative electrode materials and conductive carbon black prepared in Examples 1-2 and Comparative Examples 1-8 were ground in a mortar to make them uniformly mixed, added to a PVDF N-methylpyrrolidone (NMP) solution, stirred uniformly, and a slurry was prepared, wherein the mass ratio of negative electrode material: conductive carbon black: PVDF was 90:5:5, and the slurry was coated on a copper foil, dried, and rolled to form a negative electrode sheet. A metal lithium sheet was used as a counter electrode, Celgard2400 was used as a diaphragm, and 1 mol / LLiPF6 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + EMC (ethyl methyl carbonate) (volume ratio 1:1:1) was used as an electrolyte. A simulated battery was assembled in an argon-filled glove box, and after standing for 12 hours, the first charge specific capacity and the first coulomb efficiency were measured.

[0098] In the charge and discharge voltage range of 2.5-4.2V, the cycle test performance was tested at different temperatures (25℃, -20℃, 50℃) and a charge and discharge rate of 1.0C / 1.0C.

[0099] Table 1 Performance test results

[0100]

[0101]

[0102] From the above performance test results, it can be seen that the negative electrode materials of Examples 1-2 are used to prepare batteries with high capacity, high initial coulombic efficiency, good cycle performance, good temperature resistance, and excellent electrical properties. In particular, the comprehensive performance of Example 1 is the most outstanding.

[0103] However, the comparative examples are significantly worse than the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. Comparative Example 1 changes the weight ratio of carbon nanotubes, and it can be seen that the battery's capacity and cyclability at room temperature decrease. Comparative Example 2 changes the parameters of carbon nanotubes, and it can be seen that the battery's cyclic performance at high temperature decreases. Comparative Examples 3 and 4 change the ratio of unsaturated monomers containing epoxy groups and monomers containing carbon-carbon double bonds, and it can be seen that the cyclic performance of the lithium battery at low temperatures decreases. Comparative Example 5 changes the parameters of nanosilicon, and the cyclic performance of the lithium battery at high temperatures decreases. Comparative Example 6 Nanosilicon is not modified and is prepared by a carbonization method. It can be seen that the comprehensive performance of the battery decreases significantly. Comparative Examples 7 and 8 have different surfactants, and the coulombic efficiency of the battery decreases. The above experimental results further demonstrate the importance of the technical solution defined in the present invention for its technical effects.

[0104] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material based on modified carbon nanotubes, characterized in that: The following steps are involved: Step 1: Preparation of modified carbon nanotubes: (1) mixing carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in a weight ratio of 1: (30-35), stirring evenly, heating in a water bath at 50-60° C. for 2-3 h, washing with water until neutral, and drying to obtain pretreated carbon nanotubes; (2) adding 1 part by weight of the pretreated carbon nanotubes to 90-100 parts by weight of a mixed solvent of ethanol / water, adjusting the pH to 9-9.5 with aqueous ammonia, adding 2.0-2.5 parts by weight of KH550 dropwise, reacting at 40-45° C. for 12-15 hours, filtering, washing, and drying to obtain silane-modified carbon nanotubes; (3) dispersing 0.5 parts by weight of silane-modified carbon nanotubes in 50-55 parts by weight of dimethylformamide, adding 1.5-1.7 parts by weight of unsaturated monomers containing epoxy groups and 1.5-1.7 parts by weight of monomers containing carbon-carbon double bonds, heating to 60-65° C. under nitrogen protection, adding 0.13-0.15 parts by weight of azobisisobutyronitrile, and continuing to heat to 80-85° C., reacting for 3-5 hours, cooling to room temperature, washing, and drying to obtain modified carbon nanotubes; Step 2: Preparation of modified nano-silicon: (1) placing nano-silicon in a H2SO4 / H2O2 mixed solution with a volume ratio of (3-4):1, stirring at 80-90°C for 2-3h, filtering, washing, and drying to obtain pretreated nano-silicon; (2) dissolving 1 part by weight of pretreated nano-silicon and 0.3-0.5 parts by weight of 3-aminopropyltriethoxysilane in 12-15 parts by weight of anhydrous toluene, reacting under reflux at 60-70° C. for 20-22 hours, separating the solid from the liquid, washing, and vacuum drying to obtain modified nano-silicon; Step 3: Preparation of negative electrode materials: (3) 5.2-5.5 parts by weight of modified nano-silicon, 1 part by weight of modified carbon nanotubes, 0.1-0.3 parts by weight of a surfactant and 10-12 parts by weight of ethanol are mixed, the temperature is raised to 60-65°C, and the mixture is stirred for 0.5-1h. The pH value is adjusted to 8.0-8.2 with aqueous ammonia, and then 8-10 parts by weight of water are added. The mixture is kept warm for reaction for 12-15h. After the reaction is completed, the mixture is filtered, washed and dried to obtain a negative electrode material based on modified carbon nanotubes.

2. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution of concentrated sulfuric acid and concentrated nitric acid is (3-4):

1.

3. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol / water mixed solvent is (3-4):

1.

4. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The unsaturated monomer containing epoxy group includes glycidyl methacrylate and allyl glycidyl ether in a weight ratio of (2-4):

1.

5. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The monomer containing carbon-carbon double bonds comprises methyl methacrylate, isooctyl methacrylate and butyl acrylate in a weight ratio of 1:(1.2-1.4):(0.3-0.6).

6. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The particle size of the nano silicon is 10-50nm, the average particle size is 35nm, and the specific surface area is 42.4m 2 / g.

7. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The carbon nanotubes are a mixture of single-walled carbon nanotubes, double-walled carbon nanotubes and multi-walled carbon nanotubes in a weight ratio of 1:(1.2-1.5):(0.6-0.8).

8. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 7, characterized in that: The single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g, conductivity is 2400s / cm; double-walled carbon nanotubes have a diameter of 2-4nm, a length of 0.5-2μm, and a specific surface area of ​​450m 2 / g, conductivity is 150s / cm; the diameter of multi-walled carbon nanotubes is 5-15nm, the length is 0.5-2μm, and the specific surface area is 45m 2 / g, conductivity is 120s / cm.

9. The method for preparing a negative electrode material based on modified carbon nanotubes according to claim 1, characterized in that: The surfactant is a mixture of polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and diethanolamide in a weight ratio of 1: (1.2-1.4): (0.3-0.6).

10. A negative electrode material based on modified carbon nanotubes obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano silicon / carbon composite material, preparation method and lithium ion battery containing nano silicon / carbon composite material as negative electrode material

    CN108470899A

  • Modified silicon-based negative electrode material and preparation method and application thereof

    CN116722115A

  • Electrode and power storage element using it

    JP2007242386A

  • Silicon-based Anode Active Material for Secondary Battery and Method for Preparing the Same

    KR102500979B1

  • Production method for negative electrode for all-solid-state battery, and negative electrode for all-solid-state battery

    US20170141395A1